The sixth-century city in the Roman East: survival or demise of the traditional urban context? - Jacobs, I (Routledge, 2018)
This chapter examines how representative the philhellenic opinions of the School of Gaza for sixth-century city-dwellers at large by discussing the contemporary urban environment. By the start of Late Antiquity, the Greek tragedies and comedies that associate with classical theatre had already been largely replaced by other kinds of shows, the most important being the mimes and pantomimes. Both genres often were strongly reminiscent of paganism. Mimes were a very old form of farce, performed by troupes of male and female actors, the plots of which were based on daily life or ancient myths. The North Theatre of Gerasa could accommodate between 2,200 and 2,800; the city’s larger South Theatre could accommodate 5,000–6,300. There can be no doubt that the theatre initially remained highly popular in large areas of the late antique East. Laws of the end of the fourth century confirm that the imperial government encouraged the continuance of spectacles and festivals.